Effect of Relaxation Exercises on Vitality of Primigravida Women Attending Prenatal Clinics in Toyserkan, Hamadan - Farzaneh Soltani; Parisa Parsa; Samereh Ghelichkhani; Ghodratollah roshanaei (Hamadan University of Medical Sciences, 2017)
Background: Vitality, as one of the components of well-being, decreases during pregnancy. This study investigate the effect of relaxation exercises on vitality of primigravida women in Hamadan, Iran. Methods: The present quasi-experimental study was conducted on 100 primigravida women referring to a prenatal care center. Before the intervention, all the pregnant women completed the vitality and demographic characteristics questionnaires. The pregnant women of the intervention group participated in 8 sessions every two weeks with an emphasis on physical and relaxation exercises, while, the control group received the routine care of the prenatal clinic. By the end of the sessions, the questionnaires were recompleted by both intervention and control groups and compared inter and intra two groups. Results: The mean score of vitality of the women in the intervention group was 31/7±58/33 before intervention which has reached 55/4±32/38 after intervention, indicating a significant difference (p <0.05); while, the mean score of the vitality of the women in the control group was reduced (from 71/7±32/36 to 30/7±96/27), so that it significantly differed from the pre-intervention state (p <0.05). Conclusion: The present study documented the importance of the relaxation exercises as a simple and available health intervention, which could lead to the increased vitality in pregnant women.